DIE BETEKENIS VAN SPORT AS ‘N FISIEK-REKREATIEWE AKTIWITEIT MET BESONDERE VERWYSING NA DIE MILITÊR - Geyer, G.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
The industrialization of society has contributed greatly to decreasing physical exertion by man. Less emphasis on characteristics like courage and perserverance often associated with physical activities, can be found in the work pattern of man of today. Sport is presented as an activity which can involve man in an informal way socially, emotionally and physically. Important theoretical views on social, educational and psychological aspects of sport participation are described. In the Military field sport plays an important role in the physical and mental preparation of the soldier.